Study The Post–Covid–19 Academic Challenges of The School Heads in District Shaheed Benazirabad - Siddique, Uzma; Zarif, Dr. Tayyaba (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2025)
The emergence of COVID-19 in Wuhan in December 2019 made every country to take notice of the situation and announce globally accepted effective measures to minimize the losses. This pandemic situation has shaken every pillar of the states in the world. Education is a continuous process, and the mixing up of the masses from different corners of society was supposed to be a major cause of its spread. The shutdown of educational institutions was the very first step taken by each country to curtail the spread of COVID-19. The same steps were rigorously taken in Pakistan as well. The reopening of the schools took almost seven months, but during this period, some online classes were taken at higher education level At the school level, it was also a big challenge because of the insufficient resources and difficulties to use technology. The schools were reopened under the SOPs by the Government of Pakistan and the provincial governments and their departments and so the education department also notified the SOPs for the schools to re-continue the education without a visible loss. The reopening of the schools was not an easy task as the parents and the students were afraid of becoming affected by the virus. This study was intended to study the post-COVID-19 academic challenges of the school heads in District Shaheed Benazirabad. The objectives of the research study were to determine the challenges faced in the implementation of SOPs, analyze the support from the higher authorities, and understand the head teachers’ administrative and management challenges after the reopening of the schools in district Shaheed Benazirabad. The quantitative research method was applied in this research study and a survey design was employed. The population of the research study was 245 head teachers of the Elementary, Middle, Secondary, and Higher Secondary boys’ and girls’ schools of District Shaheed Benazirabad. The sample of the current study was 174 headteachers (43+42+44= 174) selected through a simple random sampling technique. A self-designed questionnaire on a five-point Likert scale was used for data collection. The results showed that in some cases the necessary facilities were missing in the schools, it was also found that the higher authorities though responded positively but yet some of the headteachers showed concerns. It was also found that the teachers faced problems in managing the proper seating of the students in overcrowded classes during the COVID-19 pandemic situation. It is recommended that the teachers and the head teachers should be made prepared to tackle any such situation in the future, the necessary support should be made available in time in the schools, and the higher authorities should engage focal persons for a cluster of schools to keep in touch with the headteachers to cope up with such situations.